Microsoft Office 2019 all-in-one - Weverka, Peter (Hoboken, NJ : John Wiley & Sons, Inc., 2019)
Microsoft Office is the productivity tool used in homes and workplaces around the globe. Getting the most out of Office requires you to be part mathematician, part graphic designer, part storyteller, part database architect, and part wizard. Or you can just consult with the simple steps in this book to get results from Office's application. It's a crash course in every part of the Office suite, with valuable tips for making the most out of Office.
Introduction -- Common office tasks -- Word 2019 -- Excel 2019 -- Powerpoint 2019 -- Outlook 2019 --Access 2019 -- Publisher 2019 -- Working with charts and graphics -- Office 2019: one step beyond -- File sharing and collaborating.
"10 books in one!" --Cover.
Includes index.
Keywords: Microsoft Office; Microsoft Word; Microsoft Excel (Computer file); Microsoft PowerPoint (Computer file); Microsoft Access; Microsoft Outlook; Microsoft Publisher; Microsoft Access; Microsoft Excel (Computer file); Microsoft Office; Microsoft Outlook; Microsoft PowerPoint (Computer file); Microsoft Publisher; Microsoft Word; Integrated software; Word processing; Electronic spreadsheets; Presentation graphics software; Database management -- Computer programs; Personal information management -- Computer programs; Desktop publishing; Business -- Computer programs; Microsoft Word; Microsoft Office; Microsoft Excel (Computer file.); BUSINESS & ECONOMICS / Office Management; Business -- Computer programs; Database management -- Computer programs; Desktop publishing; Electronic spreadsheets; Integrated software; Personal information management -- Computer programs; Presentation graphics software; Word processing